2019
DOI: 10.1002/jcp.28073
|View full text |Cite
|
Sign up to set email alerts
|

The phosphoinositide hydrolase phospholipase C delta1 inhibits epithelial‐mesenchymal transition and is silenced in colorectal cancer

Abstract: In this study, we found that the phospholipase C delta1 (PLCD1) protein expression is reduced in colorectal tumor tissues compared with paired surgical margin tissues. PLCD1‐promoted CpG methylation was detected in 29/64 (45%) primary colorectal tumors, but not in nontumor tissues. The PLCD1 RNA expression was also reduced in three out of six cell lines, due to PLCD1 methylation. The ectopic expression of PLCD1 resulted in inhibited proliferation and attenuated migration of colorectal tumor cells, yet promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Cellular proteins were extracted and western blotting was performed as previously described [ 26 , 29 , 30 ]. Protein lysates (40 μg) were separated by sodium dodecyl sulfate‐polyacrylamide gel electrophoresis and transferred onto polyvinylidene fluoride membranes.…”
Section: Methodsmentioning
confidence: 99%
“…Cellular proteins were extracted and western blotting was performed as previously described [ 26 , 29 , 30 ]. Protein lysates (40 μg) were separated by sodium dodecyl sulfate‐polyacrylamide gel electrophoresis and transferred onto polyvinylidene fluoride membranes.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study has also demonstrated low expression of PLCD1 in colorectal cancer cells and indicated that restoring PLCD1 expression inhibited colorectal cancer cell proliferation and induced apoptosis; furthermore, restoration of PLCD1 inhibited cell proliferation, metastasis and tumorigenicity in colorectal cancer ( 21 ). In esophageal squamous carcinoma cells, PLCD1 was indicated to inhibit cell proliferation, invasion and migration by suppressing the Wnt/β-catenin signaling pathway ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to literature, cancer-associated hypermethylation was previously shown for the STK33 [34][35][36], IQSEC1 [37], and PLCD1 [38][39][40][41][42][43] genes, however, a decrease in the expression was observed only for IQSEC1 [37] and PLCD1 [38][39][40][41][42][43] (Table 4). CSRNP1 and C6orf141 were found to be downregulated with no studied methylation status.…”
Section: Differentially Methylated Cpg Sites Associated With the Highmentioning
confidence: 90%
“…Notably, aberrant methylation of the STK33, and PLCD1 genes was observed in other cancers. In particular, often promoter hypermethylation of the PLCD1 gene was shown to be associated with its downregulation in breast [38], gastric [39], and colorectal cancers [40], as well as chronic myeloid leukemia [41]. In colorectal cancer, PLCD1 promoter hypermethylation and its decreased expression were correlated with tumor progression [42].…”
Section: Discussionmentioning
confidence: 99%